Praktik Manajemen Kurikulum : Rendahnya Daya Literasi Peserta Didik pada Sekolah Dasar - Mashun, Mashun (Jurnal Pendidikan, Sains, Geologi, dan Geofisika (GeoScienceEd Journal), 2025)
This study aimed to analyze curriculum management practices related to the low literacy levels of elementary school students in terms of content, approach, and implementation. The research used a descriptive qualitative approach. Data collection techniques included: observations of teaching and learning activities to directly examine the integration of literacy into the learning process; in-depth interviews with principals and teachers to gather information on curriculum implementation and literacy activities; and documentation studies such as lesson plans (RPP), textbooks, students’ literacy assessment results, and curriculum documents. The data were analyzed through data reduction, data presentation, and conclusion drawing. Data validity was ensured through triangulation of sources and techniques by comparing the results of interviews, observations, and document analysis. The results showed that in terms of content: curriculum changes were not accompanied by extensive teacher training, there was a lack of textbooks that promoted literacy activities, and support from the school was insufficient. In terms of approach: teachers tended to use lecture methods, and learning strategies were no longer student-centered. In terms of implementation: planning for the integration of literacy programs into the school curriculum was inadequate, teacher training on literacy-based learning strategies was rarely implemented, and evaluation and follow-up activities on students’ literacy results were minimal. These were the main factors that contributed to low literacy achievement. This study recommends strengthening the planning, implementation, and evaluation functions of a literacy-based curriculum as a strategy to improve students’ literacy skills at the elementary school level.